OPTIMALISASI POLA KEPEMIMPINAN VISIONER, KOMPENSASI DAN PENEMPATAN KERJA DALAM MENINGKATKAN KINERJA PEGAWAI - Syafruddin, S; Saputri, Ayu Angrayani (Fakultas Ekonomi dan Manajemen, 2025)
This study aims to examine the effect of visionary leadership patterns, compensation and job placement on employee performance at the Regional Secretariat of Sumbawa District. The type of this study used was associative study with a quantitative approach. The type of data used in this study was quantitative data obtained directly from research respondents using a questionnaire. The respondents in this study were 53 employees of the Regional Secretariat of Sumbawa District. The number of respondents was determined using the Slovin formula and selected using probability sampling techniques with a simple random sampling method. The data analysis techniques used include multiple linear regression analysis, partial hypothesis testing (t-test), simultaneous hypothesis testing (F-test), and coefficient of determination testing (R2). The results of this study showed that visionary leadership patterns, compensation, and job placement had a positive and significant effect on employee performance at the Regional Secretariat of Sumbawa District, both partially and simultaneously. The effect of visionary leadership patterns, compensation, and job placement on employee performance at the Regional Secretariat of Sumbawa District was 92%, while the remaining of 8% was effected by other variables outside this research model, such as work motivation, job satisfaction, and work discipline.